THE EFFECT OF ROE, EPS, AND ROA RATIOS ON THE PRICE PERFORMANCE OF BSDE AND PWON IN 2019-2023 - Monalisa, Monalisa; Afifah, Eka Fitriatul; Kartikasari, Fahreza Febianti (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze the influence of Return on Equity (ROE), Earnings Per Share (EPS), and Return on Assets (ROA) on stock prices in two leading companies in the Indonesian property sector, namely PT Bumi Serpong Damai Tbk (BSDE) and PT Pakuwon Jati Tbk (PWON), during the 2019-2023 period. The research is expected to provide useful insights for investors and other stakeholders in making better investment decisions. Method: The research employs a quantitative approach by using secondary data sourced from financial statements accessed through the official website of the Indonesia Stock Exchange. The study applies panel data regression models using the Common Effect Model, Fixed Effect Model, and Random Effect Model, with STATA 17 as the statistical tool. Several tests, including the Chow Test, Hausman Test, and Lagrange Multiplier Test, are conducted to determine the most suitable model. Classical assumption tests, such as normality, multicollinearity, and heteroscedasticity tests, are also performed to validate the regression model. Results: The results show that ROE, EPS, and ROA simultaneously have a significant influence on stock prices. However, based on partial tests, only EPS significantly affects stock prices in both companies. The R-squared value of 0.7457 indicates that 74.57% of the variation in stock prices can be explained by the independent variables (ROE, EPS, and ROA), while 25.43% is influenced by other factors outside the model. Novelty: This study contributes to the existing literature by focusing on the Indonesian property sector and examining the role of financial performance indicators in determining stock prices. The findings highlight the dominant impact of EPS compared to ROE and ROA, providing valuable insights for investors in assessing stock valuation within this industry.